2018
DOI: 10.1186/s13034-018-0245-0
|View full text |Cite
|
Sign up to set email alerts
|

Somatic symptoms in adolescence as a predictor of severe mental illness in adulthood: a long-term community-based follow-up study

Abstract: BackgroundSomatic symptoms are common and costly for society and correlate with suffering and low functioning. Nevertheless, little is known about the long-term implications of somatic symptoms. The objective of this study was to assess if somatic symptoms in adolescents with depression and in their matched controls predict severe mental illness in adulthood by investigating the use of hospital-based care consequent to different mental disorders.MethodsThe entire school population of 16–17-year-olds in the cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 48 publications
4
46
0
1
Order By: Relevance
“…43 It has been suggested that early treatment of adolescent somatic symptoms should have a high priority because of the increased risk of subsequent poor mental health outcomes. 11 Interventions that reduce symptoms and reduce the number of visits to school health care services and mental health services are warranted. Dance intervention may be an example of an active, costeffective, nonpharmacological complementary treatment for this target group.…”
Section: Discussionmentioning
confidence: 99%
“…43 It has been suggested that early treatment of adolescent somatic symptoms should have a high priority because of the increased risk of subsequent poor mental health outcomes. 11 Interventions that reduce symptoms and reduce the number of visits to school health care services and mental health services are warranted. Dance intervention may be an example of an active, costeffective, nonpharmacological complementary treatment for this target group.…”
Section: Discussionmentioning
confidence: 99%
“…This association was only partly explained by contextual factors, indicating that adolescents suffering from an extended episode of depression are predisposed to future mental health problems 22. Similarly, multiple somatic symptoms in adolescence independently predicted continued depressive episodes and other mental health concerns in early adulthood 89 90. Register-based data showed that females with adolescent depression had an increased consumption of both inpatient and outpatient care, but also more prescribed psychotropic as well as non-psychotropic drugs in early adulthood.…”
Section: Findings To Datementioning
confidence: 99%
“…In the past, they were usually defined as medically unexplained symptoms or functional somatic symptoms (Cerutti et al, 2016). The rising occurrence and persistence until the age of adulthood (Bohman et al, 2018), but especially the fact that they significantly decrease one's quality of life, have resulted in a proposal to include a new category of "Somatic Symptom and Other Related Disorders" within the Diagnostic and Statistical Manual of Mental Disorders (DSM-5, 2013). Regardless of the formal definition, these health issues have been occurring in children and adolescents rather frequently for decades and their origin is often too difficult for doctors to determine explicitly because it stems from psychological aetiology.…”
Section: Introductionmentioning
confidence: 99%